Entrepreneurship - Roy, Rajeev (Oxford University Press, 2008)
Entrepreneurship Management is a comprehensive textbook in the Indian context for management students. It is meant to familiarize students with the ground realities of starting and managing their own business. The book has recent research inputs on entrepreneurship